Rationale for the use of N‐acetylcysteine in both prevention and adjuvant therapy of COVID‐19. Issue 10 (11th August 2020) - De Flora, Silvio; Balansky, Roumen; La Maestra, Sebastiano
Abstract: COVID‐19 may cause pneumonia, acute respiratory distress syndrome, cardiovascular alterations, and multiple organ failure, which have been ascribed to a cytokine storm, a systemic inflammatory response, and an attack by the immune system. Moreover, an oxidative stress imbalance has been demonstrated to occur in COVID‐19 patients. N ‐ Acetyl‐L‐cysteine (NAC) is a precursor of reduced glutathione (GSH). Due to its tolerability, this pleiotropic drug has been proposed not only as a mucolytic agent, but also as a preventive/therapeutic agent in a variety of disorders involving GSH depletion and oxidative stress. At very high doses, NAC is also used as an antidote against paracetamol intoxication. Thiols block the angiotensin‐converting enzyme 2 thereby hampering penetration of SARS‐CoV‐2 into cells. Based on a broad range of antioxidant and anti‐inflammatory mechanisms, which are herein reviewed, the oral administration of NAC is likely to attenuate the risk of developing COVID‐19, as it was previously demonstrated for influenza and influenza‐like illnesses. Moreover, high‐dose intravenous NAC may be expected to play an adjuvant role in the treatment of severe COVID‐19 cases and in the control of its lethal complications, also including pulmonary and cardiovascular adverse events.